2014
DOI: 10.1371/journal.pone.0109207
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Risks of Foster Care Placement for Danish Children

Abstract: Although recent research suggests that the cumulative risk of foster care placement is far higher for American children than originally suspected, little is known about the cumulative risk of foster care placement in other countries, which makes it difficult to gauge the degree to which factor foster care placement is salient in other contexts. In this article, we provide companion estimates to those provided in recent work on the US by using Danish registry data and synthetic cohort life tables to show how hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…Our observed cumulative incidence of about 2.2% is lower than the cumulative incidence between ages 1 and 18 from U.S. population‐based research that found an overall incidence 4.2% . This is consistent with previous population‐based research in Denmark demonstrating that the difference in cumulative risks between the two countries has increased over time . For this reason, one could argue that a study focused on this outcome may not be applicable outside an individual study setting.…”
Section: Discussionsupporting
confidence: 87%
“…Our observed cumulative incidence of about 2.2% is lower than the cumulative incidence between ages 1 and 18 from U.S. population‐based research that found an overall incidence 4.2% . This is consistent with previous population‐based research in Denmark demonstrating that the difference in cumulative risks between the two countries has increased over time . For this reason, one could argue that a study focused on this outcome may not be applicable outside an individual study setting.…”
Section: Discussionsupporting
confidence: 87%
“…In Sweden, approximately 4% of all children are at some time during their childhood placed in societal out‐of‐home care (OHC, foster family or residential care), around the same proportion as in Denmark and the UK (Fallesen, Emanuel, & Wildeman, ; McGrath‐Lone, Dearden, Nasim, Harron, & Gilbert, ; Vinnerljung, ; Vinnerljung, Hjern, Weitoft, Franzén, & Estrada, ). For several decades, studies from various Western countries have reported strikingly high levels of somatic health problems in this group of children (Arora, Kaltner, & Williams, ; Chernoff, Combs‐Orme, Risley‐Curtiss, & Heisler, ; Halfon, Mendonca, & Berkowitz, ; Hansen, Mawjee, Barton, Metcalf, & Joye, ; Kling, Vinnerljung, & Hjern, ; Nathanson & Tzioumi, ; Schor, ; Steele & Buchi, ; Turney & Wildeman, ; Zewdu, ).…”
Section: Introductionmentioning
confidence: 99%
“…Wildeman and Emanuel (2014), found that 15.4% of Native American children and 11.5% of African-American children in the population entered care by age 18 compared to 4.9% of White children. More recently, the value of cumulative incidence rates for comparing the impact of differing state or national policies has been recognised (Fallensen, Emanuel, & Wildeman, 2014;Mc Grath-Lone et al, 2016). This paper builds on previous research by providing cumulative incidence rates for entry to out-of-home care in Australia and Canada, as well as examining trends over time and comparing a range of risk factors for overrepresentation in out-of-home care.…”
Section: Introductionmentioning
confidence: 99%